Figure 1 from: Sikes D, Stockbridge J (2013) Description of Caurinus tlagu, new species, from Prince of Wales Island, Alaska (Mecoptera, Boreidae, Caurininae). ZooKeys 316: 35-53. https://doi.org/10.3897/zookeys.316.5400 - Sikes, Derek; Stockbridge, Jill (Zenodo, 2013)
Figure 1 - Sixteen sites at which Caurinus tlagu specimens were found, north end of Prince of Wales Island, Alaska. Table 1 lists site and specimen data, also available online at http://arctos.database.museum/saved/Caurinus-AK. TL = type locality.